Water Quality of The Karedok Weir in Kecamatan Jatigede, Kabupaten Sumedang, West Java Province as a Source of Raw Water for Drinking Water - Wulandani, Aris; Nurhasanah, Nurhasanah; Ridhowati, Sherly (Sriwijaya Journal of Environment, 2024)
Clean water is a funWeirental human need. This need for clean water can be met from groundwater and surface water. One of the potential sources of clean surface water is water from Weirs or lakes. This study aimed to determine the quality of water from Karedok Weir in Kecamatan Jatigede, West Java Province, and compare it with the Regulatory Limit in Appendix VI No. 22 of 2021 on the Implementation of Environmental Protection and Management. The research tested physical, chemical and bacteriological parameters in 4 locations, namely upstream of the Cimanuk River, downstream of the Cimanuk River, Karedok Weir 1 and Karedok Weir 2. The results were then compared with the national water Regulatory Limit according to Attachment VI of Government Regulation of the Republic of Indonesia No. 22 of 2021 Class 1 Water Group, water quality for drinking raw water as well as other uses that require the same water quality. All data series at all sampling sites were analysed for their status using the STORET method developed by the US EPA. Concluded that the water at the Karedok Weir 2, which is included in the Class A category, is very good or meets the Regulatory Limit.